Pengembangan Game Edukasi Pengenalan Bendera Negara-Negara Asia Menggunakan Construct 2 - Olani, Dede Yosep; Nugroho, Nurhasan; Munawir, Ahmad (Pusat Riset dan Inovasi Nasional, 2025)
The development of information technology has encouraged the birth of interactive and engaging digital learning media innovations, one of which is educational games. This study aims to develop a Construct 2-based educational game that introduces flags of countries in the Asian continent to elementary school students. This game is designed to support children's visual, auditory, and kinesthetic learning styles, while addressing the limitations of conventional methods that are less interactive. The development was carried out using the Multimedia Development Life Cycle (MDLC) method through six stages: concept, design, material collecting, assembly, testing, and distribution. The resulting game consists of three main features: Learning, Quiz, and Play, which are equipped with two-dimensional illustrations, voice narration, and interactive challenges. Testing results using the Black Box method show that all features work as expected. This game is also accessible via desktop and mobile devices in HTML5 format, thus supporting flexible use both at school and at home. These findings indicate that Construct 2-based educational games can be an effective and enjoyable alternative learning medium in introducing national symbols to early childhood